PERBEDAAN STATUS GIZI PADA BALITA DENGAN ASI EKSKLUSIF DAN TANPA ASI EKSKLUSIF DI DESA KLOMPANGAN KABUPATEN JEMBER - Munawaroh, Inayatul (JURNAL ILMIAH DHDT - KEBIDANAN, 2023)
Babies who get exclusive breastfeeding will have optimally nutritionis then made them healthier, having better self devense from repeated infectious,not so easily getting allergies and sickness. For the results, babies whoget exclusively breastfeeding will grow and develop betterand optimal. The growthcan be observed from height, weight, etc. While optimal development observed from increasing motoric, psychomotoric and language. The aim of this research was to find the deferences between toddlers with and without exclusive breastfeeding in the Klompangan village Jember district. This research used comparative study by Cross Sectional approach. The respondent was 98 babies from simple random sampling, with colledted data by questioner and health indicator book. Bivariate was done by T test with p value < 0.05. This study showed that the majority of children's nutritional status was in good category with exclusive breastfeeding. After the T test was carried out, the P value (Sig. 2 tailed) was 0.000, because P-value > (α = 0.05), which meant that there was difference in not significant the nutritional status of toddlers with breastfeeding and without breastfeeding in the Klompangan village Jember district. Remembering how important of exclusive Breastfeeding it is hoped to expectant and new moms to give exclusive breastfeeding of to their babies 6 months for minimum and continuins to 2 years if it is possible.